Essential Latex Processing Plant (ELPP): A Pioneer Approach in the Production of Concentrate Latex from Local Resource to Manufacture Male Contraceptive in Bangladesh (Journal of Chemical Engineering, 2014)
For years, a respective amount of PV latex has been exported from Malaysia to manufacture male contraceptives within the country. Recently, a project titled as ELPP, has been undertaken by the Govt. Pharmaceutical Company Essential Drugs Company Ltd? to pioneer the implementation of processing natural raw latex (35-40% dry rubber content) [1] into concentrate latex (60% dry rubber content) [1] from the local resource at Modhupur region. The purpose of this project is to produce concentrate latex from local resource as the raw material for manufacturing male contraceptive instead of importing the latex from Malaysia or other countries. Several trials have been taken place to test the feasibility and productivity of the project with respect to the aspects in Bangladesh. The results and observations are found very satisfactory and the project is very much cost effective since it cuts off the foreign expense caused due to the import of concentrate latex from abroad at present days. An overall cost analysis shows that if the technology of processing concentrate latex is implemented with a proper utilization of the local resources it reduces the cost of production to a great extent. Moreover, rubber sheets produced as the byproduct from this process are very much useful and demandable in the field of rubber industries and add profit to the process. DOI: http://dx.doi.org/10.3329/jce.v27i2.17777 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 2, December 2012: 11-14